Asuhan Kebidanan Pada Ibu Hamil Trimester I Dengan Morning sickness Di PMB Helni Ramza, S.Tr.Keb di XIII Koto Kampar Tahun 2023 - Dea, Dea; Mayasari, Endang; Parmin, Joria (Evidence Midwifery Journal, 2024)
Morning sicknessis a very common condition that occurs in pregnant women, especially in the first trimester of pregnancy. In essence, morning sicknessis a normal thing, but it really needs to be given care or monitoring, because if left unchecked it can also be dangerous for the mother, including on the fetus. Factors that cause morning sicknessare hormonal changes in the body during pregnancy, namely increased estrogen and Human Chorionic Gonadotrophin (HCG) and psychological factors such as feelings of anxiety, husband’s support, social environmental factors, culture and economic conditions. This research is in the form of a case study, with descriptive observational research methods carried out at the PMB Helni Ramza on 21-26 August 2023. With the results, Ny.R 24 years old G1P0A0 UK 8 weeks with morning sickness, namely experiencing good changes from day to day, at the first visit the mother complained that she felt very often experiencing something called nausea and vomiting in the morning which made the mother weak and had no appetite, at the second visit the mother still complaining of nausea and vomiting but there has been a good change from the previous day and the results of the examination are within normal limits, on the 3rd visit the mother’s condition is getting better and the mother says she no longer experiences significant nausea and vomiting or is no longer a problem like the previous condition, and from results of examination of the mother’s condition. Thus it can be concluded that the care provided was carried out well and produced positive results.